An Analysis of Comparison on Observation Permission Letters in Selected Departments at USU: A Critical Genre Analysis - Matanari, Desna Uli; Sinar, Tengku Silvana; Pradinda, Yulia; Tarigan, Abigail Putri Chrissantha; Hasan, Hani Firlyali (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study aims to analyze the comparative observation permit letters from five study programs at the Faculty of Cultural Sciences, University of North Sumatra: English Literature, Indonesian Literature, Mandarin Language, History Sciences, and Ethnomusicology. Using a qualitative descriptive approach, this study utilizes primary data in the form of five observation permit letters and secondary data from interviews with the parties who drafted the letters. The analysis includes internal factors of the text, namely rhetorical structure (move and step) and experiential function, as well as external factors involving professional culture and administrative practices. The results of the study show variations in letter structure, language function, and administrative approach that reflect the academic needs of each study program. The observation permit letter from the Ethnomusicology study program has the most complex structure with 7 moves and 17 steps. External factors, such as organizational hierarchy and professional culture, also influence the design of the letter structure. This study provides insight into how academic institutions compile administrative documents that function as formal communication media between students and external parties. This study also highlights the importance of considering internal and external aspects in the preparation of administrative documents to ensure appropriateness to academic and professional contexts.